If it's not what You are looking for type in the equation solver your own equation and let us solve it.
x+3(x+3)=10
We simplify the equation to the form, which is simple to understand
x+3(x+3)=10
Reorder the terms in parentheses
x+(+3x+9)=10
Remove unnecessary parentheses
+x+3x+9=+10
We move all terms containing x to the left and all other terms to the right.
+1x+3x=+10-9
We simplify left and right side of the equation.
+4x=+1
We divide both sides of the equation by 4 to get x.
x=0.25
| (100/4)^-1/2 | | 7-4x=-6x+1 | | 6=x+1/x | | -7x^2+24-9=0 | | 4x/2x | | 8(x-9)=7 | | 2x+6x=12 | | 2c+6c+8+=32 | | 3(2+1)=8 | | (4x-1)/(2x^2-3) | | -2x+6=-x+5 | | =11m-3n-3s | | 2x^2-8+3=0 | | 12x-1+2x=x+1 | | -12+27x=-12 | | 10x+10x=118+x | | -3x^2-8x+35=0 | | 1x^2-5x-12=0 | | 5-2x=3x-50 | | 1/3(10x-5)=8 | | 12x=-9-4x^2 | | 1x^2+5x-10=0 | | 20x^2-66x-14=0 | | 1x^2+1x-30=0 | | 2x+1=4.5 | | x+(x+1)=156 | | -7x+7x=+1 | | 6n+6=72 | | 8+x/6=-10 | | 3(y-3)=-2y+6 | | -2x+1=-19+2x | | a^2=9a+36 |